Perceptions and parameters of preparedness of selected mothers and their daughters in the launching stage of the family - Canlas, Joy Precious D.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This study aimed to determine the perceptions of mothers and their young adult daughters of their preparedness and parameters for launching. A purposively sampled 30 Filipino daughters between the ages of 18 and 22 were interviewed. Fifteen mothers of the respondent daughters between the ages of 40 and 55 were also interviewed. The perceived preparedness was mainly referred to in terms of time-preparing now, not yet preparing, or will not prepare. On the preparedness of the daughters, daughters indicated they are preparing now, while mothers believe that their daughters are not yet preparing. On the preparedness of mothers, most daughters believe that their mothers are preparing now, while mothers are either preparing now or not yet preparing. This study also revealed that respondents are generally aware that daughters will come to a point of leaving the home, with most respondent daughters stating that leaving will be due to professionally related circumstances, while mothers believe that daughter will leave due to reasons of either profession or that they are yet to think about their daughters leaving. All daughters believe that their closeness to their mothers affect their plans for the future. Most mothers also think that their perceived closeness to their daughters influence the latter's future plans.
Thesis (Master in Family Life and Child Development)--University of the Philippines Diliman, June 2016.
Keywords: Families -- Philippines; Mothers and daughters -- Philippines